Role of Risk Control in Managing Key Employees: A Comparison of Financial Firms and Non-Financial Firms - Tabbasum, Shahana (2017)
Key employees play a crucial role in leading and contributing to the success of an organization to a prosperous route. This study aims to understand the concept of ‘key employees’ in non-financial and financial firms in Bahrain. Additionally, the study also aims to unravel the impact of risk control measures in managing key employees in distinct organizations focused in Bahrain and attempts to determine any disparities between the two industries. The relationship between the implementation of risk controls and key employees has not been explored in the past literature. This study will be examined in relevance to three types of risks: fraud risk, turnover risk and business risk. The study is significantly based on literature review and the data collected from questionnaires sent to 71 top, middle and lower level managers working in Bahrain. The findings unveil that both non-financial and financial industries implement effective risk controls to manage risks in relevance to key employees. To some extent, financial institutions seem to be better at controlling risks associated with key employees.